Knowledge management audit of Team Def an evaluation of the knowledge management system of a pre-sales team in company ABC - Pestano, Sheena Kathrine Umali
--This case study investigates the current capabilities and infrastructures of the informal knowledge management system that Team DEF has. These can be used in classifying the Knowledge Maturity Level of the team's Knowledge Management system. Acknowledging this level can influence the team to decide which structures and processes can be used in leveraging its performance and dynamics. The activities of the team can also be classified based on their perceived importance and effectiveness of sharing knowledge. This helped point out activates that the team thinks needs some improvement. It also identified opportunities that the team can consider venturing into. These opportunities can be used in planning the different possible future paths of the team and what steps must be taken to realize these opportunities. Some of the strengths of the team that can help in accomplishing its tasks and can possibly use in expanding its reach, were also recognized. These strengths can also be used in planning strategies to realize the pinpointed opportunities. This probe was executed through a series of surveys.--